Retraction: Time Series Based Gene Expression Profiling Algorithm for Stomach Cancer Diagnosis - Teresa Abuya; Bayu Priyatna (Information System; Universitas Buana Perjuangan Karawang, 2022)
Retraction to: Teresa Abuya. & B Priyatna. (20202). Time Series Based Gene Expression Profiling Algorithm for Stomach Cancer Diagnosis. Into Another Journal This article has been withdrawn by the publisher for the following reasons: This is based on the author's acknowledgment to the editor that the author has committed a violation of publication ethics. The author canceled the publication after the article was published, arguing that the template from the publisher was not standard even though the publisher had made a standard template that refers to IEEE. As such this article constitutes a grave abuse of the scientific publishing system.